Keefektivan Pembelajaran Secara Online Terhadap Perkembangan Fisik Motorik Anak - Wahyuni, Sri; Puspitasari, Ratna Nila (Institut Agama Islam Negeri Ponorogo, 2021)
The problem in this research is that in the online learning process the teachercannot monitor the physical development of the child's motor skills, because children studyat home and at home, the children cannot freely leave the house to play or go recreation.As a result, many parents think that playing cellphones is the main solution. The purposeof this study was to determine the effectiveness of online learning on motoric physicaldevelopment. The benefits of this research are expected to provide insight, boththeoretically and practically, for researchers in accordance with the focus of the researchbeing carried out. This research is a descriptive study, while the research information is asource of reference as well as previous research. Data collection was carried out by meansof observation, interview and documentation techniques. The instrument used by theresearcher was a physical motor indicator. Data analysts use an interactive analysis modelby collecting data, reducing data, presenting data, and drawing conclusions. The results ofresearch on children's physical motor development during online learning have decreased.